2020
DOI: 10.1038/s41586-020-2552-x
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic regulator function through mouse gastrulation

Abstract: Summary paragraph: During ontogeny, proliferating cells become restricted in their fate through the combined action of cell-type specific transcription factors and ubiquitous epigenetic machinery, which recognize universally available histone residues or nucleotides but are nonetheless deployed in a highly context-dependent manner 1 , 2 . The molecular functions of these regulators are generally well understood, but assigning direct developmental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
159
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(170 citation statements)
references
References 81 publications
9
159
2
Order By: Relevance
“…Lineage priming, cell fate specification and tissue patterning during early mammalian development are complex processes involving signals from surrounding tissues, mechanical constraints, and transcriptional and epigenetic changes, which together prompt the adoption of unique cell fates 17 . All of these factors play key roles in gastrulation, the process by which the three germ layers emerge, and the body axis is established.…”
Section: Introductionmentioning
confidence: 99%
“…Lineage priming, cell fate specification and tissue patterning during early mammalian development are complex processes involving signals from surrounding tissues, mechanical constraints, and transcriptional and epigenetic changes, which together prompt the adoption of unique cell fates 17 . All of these factors play key roles in gastrulation, the process by which the three germ layers emerge, and the body axis is established.…”
Section: Introductionmentioning
confidence: 99%
“…Novel imaging techniques will reveal the spatio-temporal dynamics of enhancer–promoter interactions in living cells, allowing greater understanding of how and when proximity is required developmentally [ 211 , 212 ]. Improved genomic approaches allowing resolution at the single-cell level coupled with elegant genetic and pharmacological perturbation techniques will increase our understanding of how and when chromatin states are established and decommissioned developmentally [ 213 , 214 ]. New protocols to perform multiple ‘omics’ experiments at the single cell level will result in greater understanding of the relationship between chromatin states and transcriptional output [ 215 , 216 ].…”
Section: Resultsmentioning
confidence: 99%
“…A landmark study in the field showed that in Dnmt1 knockout embryos, maintenance of XCI is unaffected in the extraembryonic endoderm while XCR takes place in the embryonic lineage [ 103 ]. A more recent study that combined genetic perturbations with single-cell RNA sequencing (scRNA-seq) in mouse embryos confirmed the role of Eed in maintenance of imprinted XCI in the TE [ 128 ]. However, Eed knockout had little impact on maintenance of XCI in the PE, indicating that distinct mechanisms maintain imprinted XCI in TE and PE lineages [ 128 ].…”
Section: Maintenance Of XCImentioning
confidence: 99%
“…A more recent study that combined genetic perturbations with single-cell RNA sequencing (scRNA-seq) in mouse embryos confirmed the role of Eed in maintenance of imprinted XCI in the TE [ 128 ]. However, Eed knockout had little impact on maintenance of XCI in the PE, indicating that distinct mechanisms maintain imprinted XCI in TE and PE lineages [ 128 ]. Given that humans have no imprinted XCI, and also have a much longer development and gestational period compared with mice, it will be interesting to define the factors and mechanisms involved in induction, maintenance and reversal of XCI in human extraembryonic lineages, which is discussed in Section 10 .…”
Section: Maintenance Of XCImentioning
confidence: 99%